Application of a vocational maturity program in students of secondary school victims of social marginalization - Cavero Reap, Rocio del Pilar (2020)
The present research work, "Program" I decide my future "in vocational maturity, in students who are victims of social marginalization of the 4th grade of the advanced cycle of CEBA Herman Busse de la Guerra, 2095, 2018.", sought to know the effects it produces the intervention of a vocational guidance plan, made up of workshops based on psychopedagogical principles, and whose didactic application is based on the objectives and principles of the proposal. The research was of an applied type, of a pre-experimental design. The study group consisted of 84 students, distributed in 42 in the experimental group and 42 in the control group. The pre-test was applied using the emotional maturity questionnaire where scores were obtained in the emotional maturity dimension (t = 1.21, p = 0.23), in the planning dimension (t = 0.62, p = 0.54), the exploration dimension (t = 1.11, p = 0.27), the information dimension (t = 1.11, p = 0.27) and finally in the decision-making dimension (U = 844, p = 0.73) showing that there are no statistically significant differences in the pretest in the experimental group and control group. The post-test results show us that after having applied the vocational program, the control and experimental groups did show significant differences in its five dimensions: In emotional maturity (t = 9.28, p = 0.00), in the planning dimension (t = 0.62, p = .001), in the exploration dimension (t = 4.865, p = 0.000), in the information dimension (U = 314.5, p = 0.000), and in the decision-making dimension (U = 71.00, p = 0.000). The study verified the effectiveness of the program "I decide my future"